HIV viral suppression results in higher antibody responses in HIV-positive women vaccinated with the quadrivalent human papillomavirus vaccine. Issue 40 (14th September 2016) - ,; Alimenti, Ariane; Dobson, Simon; Hankins, Catherine; Hill, Janet; Krajden, Mel; McAlpine, Jessica; Pick, Neora; Singer, Joel; Stone, Sarah; Summers, Marcie; Tan, Darrell; et al.
Highlights: Quadrivalent HPV vaccine safe and well tolerated in HIV-positive women. High rates of seroconversion to quadrivalent HPV types in HIV-positive Women. HIV viral load was key predictor of immune response to HPV vaccine in positive women. Older HIV-positive women likely to benefit from HPV vaccination. Abstract: Objective: To evaluate the immunogenicity and safety of the quadrivalent HPV (qHPV) vaccine in HIV-positive women over 24 months. Design: Between November 2008 and December 2012, 372 women aged 15 and older were enrolled from 14 Canadian HIV outpatient clinics in an open label cohort study. The qHPV vaccine (0.5 mL) was administered intramuscularly at months 0, 2 and 6. The primary study endpoint was seroconversion to any of the HPV types targeted by the qHPV vaccine. Antibody levels were measured at 0, 2, 7, 12, 18, and 24 months. Adverse events were recorded throughout. Results: Of 372 participants enrolled, 310 (83%) received at least one dose of the qHPV vaccine and 277 (74%) received all three doses. Ninety-five percent (293/308) were seronegative for at least one vaccine type at baseline. The median age was 38 years (IQR 32–45, range 15–66), 36% were white, 44% black and 13% were of Indigenous origin. Seventy-two percent of participants had a suppressed HIV viral load (VL < 40 c/ml) at baseline, with a median CD4 count of 510 cells/mm 3 (376–695). Month 7 HPV type-specific seroconversion rates were 99.0%, 98.7%, 98.1% and 93.6% for HPV types 6, 11, 16 and 18 respectively in the per-protocol population. Participants with suppressed HIV VL at first vaccine had a 1.74–3.05 fold higher peak antibody response compared to those without ( p from 0.006 to <0.0001). Conclusions: This study is the first to examine the qHPV vaccine in HIV-positive women out to 24 months and the first to include HIV-positive women through to age 66. The qHPV vaccine was well tolerated, and highly immunogenic. As women with suppressed viral load had higher antibody responses, planning HPV vaccination to occur when persons are virologically suppressed would be optimal for maximizing immune response. Findings provide strong evidence that older HIV-positive women can still benefit from HPV vaccination. Clinical trial registration:http://www.isrctn.com/ISRCTN33674451